Spatial variation of travel time uncertainty in container shipping - Jia, Haiying (2021)
Container shipping plays an important role in economic development by providing services for unitized cargos on fixed ocean trading routes between destinations. The transit time, as well as freight cost, presents temporal and monetary costs in the global trade system. Given the fixed routing characteristic in container shipping, a study on the reliability of travel times is crucial to understand the dynamics on temporal cost in major international trades. This research investigates empirically whether there exist spatial differences in international container shipping routes by employing actual shipment data for a fleet of over 600 container vessels extracted from the Automatic Identification System (AIS). The results show that the geographic distribution of the routes have significant impact on travel time uncertainty and hence there is clear variation across international trade routes. Sailing route security, infrastructure and trade volumes in the routes are likely the underlying explanations. This research contributes to the literature in two folds. We pioneer in modelling the micro-level container invisible trade cost by computing the service uncertainty. This also provides insight of the temporal cost of international container cargo trade in terms timing reliability and its dynamic structures.